1987
DOI: 10.1172/jci113207
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of lymphatic absorption to loss of ultrafiltration and solute clearances in continuous ambulatory peritoneal dialysis.

Abstract: The contribution of peritoneal cavity lymphatic absorption to ultrafiltration kinetics and solute clearances in continuous ambulatory peritoneal dialysis was evaluated in patients with normal (group 1) and high (group 2) peritoneal permeability X area during 4-h exchanges using 2 liters 2.5% dextrose dialysis solution with 30 g added albumin. Cumulative lymphatic drainage in all continuous ambulatory peritoneal dialysis (CAPD) patients averaged 358±47 ml per 4-h exchange and reduced cumulative net transcapilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
63
0
1

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(66 citation statements)
references
References 21 publications
2
63
0
1
Order By: Relevance
“…52 The net ultrafiltration volume at the end of a PD exchange equals the cumulative net transcapillary water transport minus lymphatic absorption during the exchange. 53 We showed that lymphatic vessels are present in both the peritoneal and pleural sides of the normal rat diaphragm but are rarely detectable in the normal rat parietal peritoneum ( Figure 6). Interestingly, LYVE-1 and VEGFR-3 mRNA levels were higher in the diaphragm than the parietal peritoneal wall.…”
Section: Discussionmentioning
confidence: 83%
“…52 The net ultrafiltration volume at the end of a PD exchange equals the cumulative net transcapillary water transport minus lymphatic absorption during the exchange. 53 We showed that lymphatic vessels are present in both the peritoneal and pleural sides of the normal rat diaphragm but are rarely detectable in the normal rat parietal peritoneum ( Figure 6). Interestingly, LYVE-1 and VEGFR-3 mRNA levels were higher in the diaphragm than the parietal peritoneal wall.…”
Section: Discussionmentioning
confidence: 83%
“…Residual, intraperitoneal and net UF volumes were calculated sequentially by standard methods [1,7,8,9,10]. Formulas are listed in table 1.…”
Section: Methodsmentioning
confidence: 99%
“…There is a general consensus that the overall magnitude of this fluid loss averages 1.0-1.5 ml/min [1,2] ( 1.4-2.1 liters/day), with a re ported range (mean ± 2 SD) of 0.3-2.7 ml/ min [3]. This mean value for the patient in overall fluid balance is approximately equal to the daily net ultrafiltration.…”
Section: Introductionmentioning
confidence: 99%